2023
DOI: 10.1186/s13023-023-02801-7
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the evidence underpinning high-risk medical devices in Europe at market entry, and potential solutions

Abstract: Aim To determine the level of evidence for innovative high-risk medical devices at market entry. Methods We reviewed all Belgian healthcare payer (RIZIV-INAMI) assessor reports on novel implants or invasive medical devices (n = 18, Class IIb-III) available between 2018 to mid-2019 on applications submitted for inclusion on their reimbursement list. We also conducted a review of the literature on evidence gaps and an analysis of relevant legal and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…With the European HTA bodies, the EUnetHTA 21 initiative is establishing and piloting methods and processes for the joint scientific consultation and the joint clinical assessment,as outlined in the HTA assessment. 27 Such efforts are important for bringing about improved quality of evidence for the technology appraisal processes by HTA bodies.…”
Section: Open Accessmentioning
confidence: 99%
“…With the European HTA bodies, the EUnetHTA 21 initiative is establishing and piloting methods and processes for the joint scientific consultation and the joint clinical assessment,as outlined in the HTA assessment. 27 Such efforts are important for bringing about improved quality of evidence for the technology appraisal processes by HTA bodies.…”
Section: Open Accessmentioning
confidence: 99%
“…Indeed, it has been found that a large proportion of health apps on the European market do not meet relevant data protection requirements 24,25 . Thirdly, concerns have been raised regarding the quality and appropriateness of the studies that are deemed acceptable under the MDR to demonstrate a product's safety and effectiveness 26,27 . Lastly, the MDR-associated CE mark only aims to indicate conformity with the regulation, without seeking to provide transparency to users unfamiliar with regulatory requirements regarding which domains have been evaluated and how apps compare across these domains.…”
Section: Introductionmentioning
confidence: 99%